Perineal Lacerations and Obstetric Anal Sphincter Injuries in Diet-Controlled Gestational Diabetes: A Large Cohort Study - Eshkoli, Tamar; Amit, Karin; Bugaiski-Shaked, Adva; Stein, Liane; Baumfeld, Yael; Weintraub, Adi Y.; Rotem, Reut (American Journal of Perinatology, 2025)
Perineal lacerations are a common obstetric complication influenced by maternal and intrapartum factors. While gestational diabetes mellitus (GDM) is linked to adverse pregnancy outcomes, the impact of diet-controlled GDM (GDMA1) on perineal injury remains unclear. This study explores the relationship between GDMA1 and perineal lacerations in vaginal deliveries.A population-based retrospective cohort study was conducted at a tertiary medical center (1988–2016), including all vaginal deliveries beyond 24 weeks gestation. Women with GDMA1 were compared with those without diabetes. The primary outcomes were the rates and severity of perineal lacerations. Univariate analysis was followed by multivariable analysis, adjusting for relevant confounders.Among 250,171 deliveries, 9,640 (3.8%) were in women with GDMA1. Women with GDMA1 were significantly older and delivered earlier than non-diabetic women, although both groups delivered at term. Rates of instrumental deliveries and episiotomy were significantly higher in the GDMA1 group, and newborns were significantly larger. Perineal lacerations occurred more frequently in women with GDMA1 compared with non-diabetic women (21.2 vs. 18.8%; p < 0.001), with first-degree tears accounting for most of the difference. In multivariate analysis, GDMA1 was independently associated with an increased risk of perineal tears (OR = 1.12, 95% CI: 1.06–1.17), while mediolateral episiotomy was associated with a reduced risk of obstetric anal sphincter injury (OASIS; OR = 0.68, 95% CI: 0.53–0.87).GDMA1 is associated with a modestly increased risk of perineal lacerations, predominantly first-degree tears, but does not significantly impact severe perineal trauma. These findings suggest that women with GDMA1 can be reassured regarding the risk of severe perineal trauma. Nonetheless, individualized risk assessment remains important in guiding delivery management, particularly in the presence of other contributing risk factors.
Keywords: gestational diabetes mellitus; perineal laceration; obstetric anal sphincter injury; mediolateral episiotomy; vaginal birth